Comparison of popular sagittal cephalometric analyses for validity and reliability - Irfan Qamaruddin; Mohammad Khursheed Alam; Fazal Shahid; Sadaf Tanveer; Marvee Umer; Erum Amin (Elsevier, 2018)
Background: The analysis of skeletal relationships of jaws in the sagittal plane is of utmost importance in orthodontic diagnosis for which numerous lateral cephalometric analyses have emerged. None of the analyses is without flaws. Current study compares ANB, Wits appraisal, Beta angle, Yen angle and W angle for their validity and reliability in diagnosis of skeletal classes. Methods: Pretreatment cephalograph of 209 orthodontic patients comprised of 92 males and 117 females were selected from orthodontic archives. Radiographs were traced for ANB, Wits appraisal, Beta angle, W angle and Yen angle measurements. Patients were divided into three skeletal classes i.e. class I, II and III based on measurements and incisor classification and profile recorded from their files. ANOVA was applied to check the validity of performed analyses and Cramer's correlation was performed to find out the correlation between analyses and skeletal classes. Results: All performed analyses showed statistically significant difference in the values for all three skeletal classes p < .05. All measured analyses were found equally reliable in diagnosis of skeletal discrepancies. Conclusion: All five-skeletal cephalometric sagittal analyses are reliable and can be used in orthodontic diagnosis as alternative to each other. Keywords: Skeletal class, Sagittal analysis, Reliability, Validity